Does Neutrophil Phenotype Predict the Survival of Trauma Patients? - Mortaz, Esmaeil; Zadian, Seyed Sajjad; Shahir, Mehri; Folkerts, Gert; Garssen, Johan; Mumby, Sharon; Adcock, Ian M. (Frontiers in Immunology, 2019)
According to the World Health Organization (WHO), trauma is responsible for 10% of deaths and 16% of disabilities worldwide, which is considerably higher than those for malaria, tuberculosis, and HIV/AIDS combined. While the human suffering and death caused by injury is well recognized, injury has a significant medical care cost. Better prediction of the state of trauma patients in the days immediately after trauma may reduce costs. Multiple traumatic injuries can cause dysfunction in all systems of the body especially the immune system placing patients at high risk of infections and inflammatory complications which are often fatal. Polymorphonuclear neutrophils (PMNs) are the most abundant leukocyte in the human circulation and are crucial for the prevention of microbial disease. Significant changes in neutrophil functions such as enhanced chemotaxis, netosis and phagocytosis occur early after injury followed by prolonged functional defects such as phagocytosis, killing mechanisms, and receptor expression. Analysis of these changes may improve the prediction of the patient’s condition over time. We review the latest findings investigating the effect of trauma on neutrophil phenotype and function and discuss the predictive potential of neutrophil alterations on secondary complications in patients with traumatic injuries. Alterations in neutrophil surface markers and functions may be potential biomarkers by which to predict the outcome of trauma patients.